INFLUENCE OF EMOTIONAL INTELLIGENCE ON RESISTANCE TO EMOTIONAL BURNOUT IN TEACHERS - Daria Konstantinovna Danko (European Science Publishing, 2024)
The modern world, where stress has become the norm and overload is an inevitable companion of life, dictates its own rules. Under these conditions, emotional intelligence (EI) acquires special value, becoming the key to success in both professional and personal life.
Keywords: emotional intelligence (EI), emotional burnout, teachers, understanding other people's emotions, managing one's emotions